From mechanism to application: a look at the CuBTTri-catalyzed decomposition of S-nitrosoglutathione - Mohnike, Margaret, author; Reynolds, Melissa M., advisor; Chen, Eugene, committee member; Prieto, Amy, committee member; Clapp, Tod, committee member (Colorado State University. Libraries, 2025)
The lifetime of blood-contacting medical devices is negatively impacted by biofouling, which can lead to worse outcomes for the patient, from diminished device functioning to the risk of life-threatening medical events such as embolism. One approach to mitigating these complications is the design and construction of surface materials that help minimize the cellular events that lead to biofouling, such as thrombus formation. Although there are multiple avenues to this end that researchers are currently examining, an encouraging method is the local administration of nitric oxide (NO) at the surface of the medical device. Nitric oxide is an inorganic radical gas that is central to multiple signaling systems within the body, as well as having direct impact on platelet aggregation and bacterial control. Since it is ubiquitous in the body, there are readily available endogenous sources of NO within the blood, one such examples being S-nitrosothiols (RSNO), which are known to release the NO from RSNOs. By embedding a copper azolate metal organic framework (MOF) into the surface of medical devices, a reactive copper center can be tethered directly to the relevant location and allow for the release of NO from molecules already present in the body. Further investigation must be taken to more fully understand the system of interest, both from a structural perspective and a reactivity one, to better optimize and tune NO output for optimal release rate. In addition, to facilitate broader studies, more efficient syntheses for the water-stable MOF CuBTTri (Cu(II) benzene-1,3,5-tris(1H-1,2,3-triazoy-5-yl)) are required. Finally, having already established the ability of CuBTTri to release NO from GSNO while embedded into a polymer, the next step is to test the compatibility of this coating with a device that could be blood-contacting.In Chapter 2, a series of mechanistic studies were performed to better understand how CuBTTri releases NO from RSNOs, In Chapter 3, the organic linkers that form the MOF were deuterated to permit more in-depth structural characterization in hopes of elucidating surface features on the MOF. In Chapter 4, the synthesis of CuBTTri was optimized to be more efficient than the originally reported solvothermal method. These optimization methods also led to a much improved ability to control MOF particle size. In Chapter 5, the feasibility of incorporating MOFs into existing blood-contacting devices was tested by incorporating a MOF-polymer composite onto the surface of a glucose sensor and evaluating its impact.